Photophysics of Xanthene Dyes at High Concentrations in Solid Environments: Charge Transfer Assisted Triplet Formation - Litman, Yair Ezequiel (2018)
The photophysical behavior of two xanthene dyes, Eosin Y and Phloxine B, included in microcrystalline cellulose particles is studied in a wide concentration range, with emphasis on the effect of dye concentration on fluorescence and triplet quantum yields. Absolute fluorescence quantum yields in the solid-state were determined by means of diffuse reflectance and steady-state fluorescence measurements, whereas absolute triplet quantum yields were obtained by laser-induced optoacoustic spectroscopy and their dependence on dye concentration was confirmed by diffuse reflectance laser flash photolysis and time-resolved phosphorescence measurements. When both quantum yields are corrected for reabsorption and reemission of radiation, ΦF values decrease strongly on increasing dye concentration, while a less pronounced decay is observed for ΦT. Fluorescence concentration quenching is attributed to the formation of dye aggregates or virtual traps resulting from molecular crowding. Dimeric traps are however able to generate triplet states. A mechanism based on the intermediacy of charge-transfer states is proposed and discussed. Calculation of parameters for photoinduced electron transfer between dye molecules within the traps evidences the feasibility of the proposed mechanism. Results demonstrate that photoactive energy traps, capable of yielding dye triplet states, can be formed even in highly-concentrated systems with random dye distributions.